Influence of storage time and the variety of ginger (Zingiber officinale) on the physico-chemical properties and sensory acceptability of calamansi-ginger gel beverage. - Priza, Firstlen Grace P.
One of the most sought natural products at the height of the COVID-19 pandemic is ginger, as it possesses beneficial health effects. Ginger-based beverages have received considerable attention as a result of growing awareness of the health benefits derived from these products. However, the quality of these products can be affected by the variety and relative composition of the ginger rhizome. Moreover, as the ginger undergoes respiration after harvest, the storage time and condition can also affect its quality and innate properties such as taste, color, flavor, and aroma, which can also affect the quality of a secondary-developed food product. Therefore, this study aimed to investigate the influence of ginger varieties (Native yellow variety and Imugan variety) and storage time (fresh and stored for 3 days) on the physico-chemical properties of calamansi-ginger gel and the sensory acceptability of its dilution as a cold drink. The results of the study revealed that a significant difference was found in the moisture content of the ginger filtrate based on storage time. Meanwhile, significant differences in the pH and moisture content of the ginger filtrate, were found based on ginger variety. A significant difference was also found in the pH, moisture content, and total phenolic content of the calamansi-ginger gel based on the ginger variety used. Moreover, based on storage time, panelists identified the calamansi-ginger gel that utilized the native yellow ginger variety (fresh) as the most acceptable. Based on the ginger variety used, consumers identified the calamansi-ginger gel that utilized the Imugan variety (stored) as the most acceptable. For consumer preference, panelists preferred the Imugan variety (stored) calamansi-ginger gel beverage to the commercial product. The calamansi-ginger gel from the Imugan variety (stored) cost â‚±126.74 per 240 ml bottle.